Dynamic Capabilities as Drivers of International Intellectual property Expansion in the Anime Industry - Haffu, Kyara (My University, 2026)
Anime has achieved global prominence, but existing literature lacks firm-level analysis of the strategic capabilities required to scale and adapt within high-uncertainty international markets. This research addresses this gap by examining how Japanese multinational entertainment companies navigate the transition from domestic production to global intellectual property orchestration. The central research question investigates how dynamic capabilities influence firms’ ability to scale and adapt anime intellectual property in global markets. This study employs a comparative qualitative case study of two industry leaders: Sony and Bandai Namco. The research utilizes secondary data from corporate reports, financial disclosures, and industry publications. Data analysis was conducted through Qualitative Content Analysis (QCA), utilizing a hierarchical coding frame rooted in the dynamic capability pillars of sensing, seizing, and transforming, alongside their respective micro-foundations. The findings reveal that while both firms achieve global scaling, they utilize divergent strategic pathways. Sony employs a vertically integrated, technology-driven model focusing on platform dominance through digital global pipes, whereas Bandai Namco utilizes an ecosystem-centric "IP Axis" model focused on cross-media synchronization. The research contributed to extending the dynamic capabilities framework by redefining sensing as a permanent technological infrastructure and demonstrating how firms transform unpredictable creative processes into repeatable, structured business routines.
Keywords: Dynamic capability; Intellectual property; International expansion; Anime; Sony; Bandai Namco; Congruence Analysis